2010
DOI: 10.1097/tp.0b013e3181d05a71
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Molecular Surveillance Study Evaluating the Clinical Impact of Community-Acquired Respiratory Viruses in Lung Transplant Recipients

Abstract: Community-acquired RVIs are frequently detected in BAL samples from lung transplant patients. In a significant percentage of patients, symptomatic or asymptomatic viral infection is a trigger for acute rejection and obliterative bronchiolitis/BOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
3
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(191 citation statements)
references
References 22 publications
4
183
3
1
Order By: Relevance
“…A significantly higher rate of local adverse events was seen with ID vaccine. These included erythema (p < 0.001), induration (p < 0.001), tenderness (p < 0.001) and 3 Confidence interval per 500 mg increase in MMF dose. Analysis excludes seven patients on Myfortic.…”
Section: Hla Alloantibody and Vaccine Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly higher rate of local adverse events was seen with ID vaccine. These included erythema (p < 0.001), induration (p < 0.001), tenderness (p < 0.001) and 3 Confidence interval per 500 mg increase in MMF dose. Analysis excludes seven patients on Myfortic.…”
Section: Hla Alloantibody and Vaccine Safetymentioning
confidence: 99%
“…In addition to increased rates of lower respiratory infection with influenza, studies have also reported increased acute and chronic allograft rejection after infection, specifically in lung and kidney transplant recipients (1,(3)(4)(5). Therefore, SOT patients are recommended to receive the annual trivalent inactivated influenza vaccine (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a commonly detected copathogen identified in 24% and 30% of mixed viral and bacterial infections, respectively [3,4]. Rhinovirus infection might contribute to serious complications such as obliterative bronchiolitis and acute graft rejection in lung and stem-cell transplant recipients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common chest computed tomography finding is ground-glass attenuation; centrilobular nodules measuring 3 to 10 mm, including a tree-in-bud appearance, can also be seen (9).…”
Section: Clinical and Radiologic Presentationmentioning
confidence: 99%